2017
DOI: 10.1088/1751-8121/aa8c17
|View full text |Cite
|
Sign up to set email alerts
|

Coined quantum walks on weighted graphs

Abstract: We define a discrete-time, coined quantum walk on weighted graphs that is inspired by Szegedy's quantum walk. Using this, we prove that many lackadaisical quantum walks, where each vertex has l integer self-loops, can be generalized to a quantum walk where each vertex has a single self-loop of realvalued weight l. We apply this real-valued lackadaisical quantum walk to two problems. First, we analyze it on the line or one-dimensional lattice, showing that it is exactly equivalent to a continuous deformation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Here, C is the Grover diffusion coin [5] that inverts the amplitudes of the coin states of each vertex about their average, and S is the flip-flop shift [13] that causes the particle to hop and turn around, so S|uv = |vu . For a detailed definition of the coined quantum walk for both regular and irregular graphs, see [14].…”
Section: Introductionmentioning
confidence: 99%
“…Here, C is the Grover diffusion coin [5] that inverts the amplitudes of the coin states of each vertex about their average, and S is the flip-flop shift [13] that causes the particle to hop and turn around, so S|uv = |vu . For a detailed definition of the coined quantum walk for both regular and irregular graphs, see [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, generalizations have been introduced that allow a randomly walking quantum particle to stay put, including lazy quantum walks [7,8] and lackadaisical quantum walks [9,10]. Here, we focus on the lackadaisical quantum walk, where a single, weighted self-loop is added to each vertex [11]. This can cause faster dispersion on the line [11][12][13], and it also speeds up quantum search on the complete graph [10,11] and two-dimensional periodic square lattice (or discrete torus) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on the lackadaisical quantum walk, where a single, weighted self-loop is added to each vertex [11]. This can cause faster dispersion on the line [11][12][13], and it also speeds up quantum search on the complete graph [10,11] and two-dimensional periodic square lattice (or discrete torus) [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the seminal paper by Shenvi et al [22], coined quantum walks are being used for search algorithms [23]. Search on the two-dimensional square lattice was analyzed in [9,24,25]. Search on the hexagonal lattice was analyzed in [20], which showed that the optimal number of steps is O( √ N ln N ) and the success probability is O(1/ ln N ), where N is the number of sites, and quantum transport on the hexagonal lattice was analyzed in [26].…”
Section: Introductionmentioning
confidence: 99%